Intravenous Thrombolysis in Patients Dependent on the Daily Help of Others Before Stroke. Issue 2 (February 2016) - Gensicke, Henrik; Strbian, Daniel; Zinkstok, Sanne M.; Scheitz, Jan F.; Bill, Olivier; Hametner, Christian; Moulin, Solène; Zini, Andrea; Kägi, Georg; Pezzini, Alessandro; Padjen, Visnja; Béjot, Yannick; et al.
Abstract : Background and Purpose—: We compared outcome and complications in patients with stroke treated with intravenous thrombolysis (IVT) who could not live alone without help of another person before stroke (dependent patients) versus independent ones. Methods—: In a multicenter IVT-register–based cohort study, we compared previously dependent (prestroke modified Rankin Scale score, 3–5) versus independent (prestroke modified Rankin Scale score, 0–2) patients. Outcome measures were poor 3-month outcome (not reaching at least prestroke modified Rankin Scale [dependent patients]; modified Rankin Scale score of 3–6 [independent patients]), death, and symptomatic intracranial hemorrhage. Unadjusted and adjusted odds ratios (ORs) with 95% confidence intervals (OR [95% confidence interval]) were calculated. Results—: Among 7430 IVT-treated patients, 489 (6.6%) were dependent and 6941 (93.4%) were independent. Previous stroke, dementia, heart, and bone diseases were the most common causes of preexisting dependency. Dependent patients were more likely to die (ORunadjusted, 4.55 [3.74–5.53]; ORadjusted, 2.19 [1.70–2.84]). Symptomatic intracranial hemorrhage occurred equally frequent (4.8% versus 4.5%). Poor outcome was more frequent in dependent (60.5%) than in independent (39.6%) patients, but the adjusted ORs were similar (ORadjusted, 0.95 [0.75–1.21]). Among survivors, the proportion of patients with poor outcome did not differ (35.7% versus 31.3%). After adjustment for age and stroke severity, the odds of poor outcome were lower in dependent patients (ORadjusted, 0.64 [0.49–0.84]). Conclusions—: IVT-treated stroke patients who were dependent on the daily help of others before stroke carry a higher mortality risk than previously independent patients. The risk of symptomatic intracranial hemorrhage and the likelihood of poor outcome were not independently influenced by previous dependency. Among survivors, poor outcome was avoided at least as effectively in previously dependent patients. Thus, withholding IVT in previously dependent patients might not be justified. Abstract : Supplemental Digital Content is available in the text.